Metasurface Reconfiguration through Lithium‐Ion Intercalation in a Transition Metal Oxide. Issue 2 (25th November 2016) - Zanotto, Simone; Blancato, Alessandra; Buchheit, Annika; Muñoz‐Castro, Marina; Wiemhöfer, Hans‐Dieter; Morichetti, Francesco; Melloni, Andrea
Abstract : Tuning the phase and amplitude response of achiral and chiral metasurfaces is a key operation in optical science and technology, since it lies at the heart of devices like wavefront shapers, beam steerers, and many others. The concept of ion intercalation is bridged from the domain of electrochemistry to that of photonics, paving the way for a new class of reconfigurable optical devices.